2007
DOI: 10.1590/s0103-50532007000100023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of composted urban solid waste addition on yield and metal contents of lettuce

Abstract: Foi desenvolvido um estudo para avaliar a acumulação de Cu, Mn, Ni, Pb e Zn, em alface cultivada em Latossolo, ao qual foram adicionados compostos de resíduos sólidos urbanos provindos de uma grande cidade (Rio de Janeiro, Estado do Rio de Janeiro) e de uma pequena cidade (Coimbra, Estado de Minas Gerais). As amostras de composto foram aplicadas ao solo em doses crescentes e em diferentes tempos de contato entre o composto e o solo. Foi avaliada ainda a influência dos metais na produção de matéria fresca e sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…However, numerically higher uptake was recorded with 75% NPK +7.5 t ha -1 microbial enriched SS (T 8 : 30.56 g ha -1 and 87.32g ha -1 , respectively) over the absolute control with (T 1 : 11.34 g ha -1 and 23.10 g ha -1 ), respectively. Jordao et al (2007) [8] reported higher Ni uptake in plants with the increased dose of urban compost. The uptake of lead by both kernel and stover of maize was found to be statistically non-significant.…”
Section: Resultsmentioning
confidence: 98%
“…However, numerically higher uptake was recorded with 75% NPK +7.5 t ha -1 microbial enriched SS (T 8 : 30.56 g ha -1 and 87.32g ha -1 , respectively) over the absolute control with (T 1 : 11.34 g ha -1 and 23.10 g ha -1 ), respectively. Jordao et al (2007) [8] reported higher Ni uptake in plants with the increased dose of urban compost. The uptake of lead by both kernel and stover of maize was found to be statistically non-significant.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, two applications of 0.24 g of (NH 4 ) 2 SO 4 and 0.09 g of KCl per pot were made on the 20th and 30th days after transplanting. Twenty days after the transplanting, 10 were macerated. The roots provided only sufficient material for the determination of the metal concentrations in the total mass of each plant.…”
Section: Growth Of Lettuce and Metal Absorption By Lettucementioning
confidence: 99%